2001
DOI: 10.4102/curationis.v24i3.859
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge and practices of primary care givers regarding home-based care of HIV/AIDS children in Blantyre (Malawi).

Abstract: Knowledge is one of the major factors that promotes adherence to treatment regimens. With the current trends worldwide of home and community-based services for the management of HIV/AIDS patients, knowledge of care givers about the home care of these patients will determine the success of the programs. The purpose of this descriptive study was to explore the knowledge and practices of primary care givers of HIV/AIDS children in the provision of home care services. In this study an attempt was made to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…One exception is a survey of children living with HIV/AIDS drawn from different home-based care organizations in Blantyre, Malawi. This study shows that 94 percent of caregivers were women (E. W. Zimba and Patricia A. McInerney 2001). Another useful quantitative survey conducted in 2004, which drew caregivers purposively from four home-based care organizations across South Africa, found that 78 percent of primary caregivers were women (Homan et al 2005a).…”
Section: Gender Of Family Caregiversmentioning
confidence: 90%
“…One exception is a survey of children living with HIV/AIDS drawn from different home-based care organizations in Blantyre, Malawi. This study shows that 94 percent of caregivers were women (E. W. Zimba and Patricia A. McInerney 2001). Another useful quantitative survey conducted in 2004, which drew caregivers purposively from four home-based care organizations across South Africa, found that 78 percent of primary caregivers were women (Homan et al 2005a).…”
Section: Gender Of Family Caregiversmentioning
confidence: 90%
“…The fi ndings of this study are similar to the result of the study done in South Africa which found that there was low knowledge of Home Based Care among family care givers for PLWHA as evidenced by the substantial proportion of caregivers who wished to receive more information and education on caring for people living with HIV/AIDS (11) . Another study done in Malawi on knowledge and practice of primary care givers regarding home based care of HIV/ AIDS children revealed a gap/lack of knowledge (10) . However the study done in Ethiopia found different results in which family care givers for PLWHA reported to be knowledgeable on HBC provision (12) .…”
Section: Discussion Believed Knowledge Of Hbc For Plwha Among Family mentioning
confidence: 99%
“…A wealth of literature (e.g., Ankrah 1993, Zimba and Mclerney 2001, Benjamin 2005, van de Wouwer 2005 has been generated on HIV/AIDS and caregiving with many research studies (e.g., Tiblier et al 1989, Wong-Wylie 1997, Uys 2002 concentrating on the experiences of caregivers. These individuals are most often reported as biological grandparents and other female kin who assume full responsibility for the orphaned children.…”
Section: T Meyiwamentioning
confidence: 99%